2015
DOI: 10.1097/sla.0000000000001385
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity in Renal Transplantation

Abstract: This is the first study to describe the effects of AL induction therapy on AA renal transplant recipients beyond the first posttransplant year. Our early results suggest that AL induction therapy abolishes the disparity in renal allograft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A 2013 retrospective report by Hussain and colleagues showed that, regardless of induction (alemtuzumab or ATG), graft survival rates did not differ in African American deceased-donor kidney transplant recipients [ 43 ]. Another study has shown that alemtuzumab induction eliminates the posttransplant survival disparity between White and African American recipients by improving graft survival in all recipients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2013 retrospective report by Hussain and colleagues showed that, regardless of induction (alemtuzumab or ATG), graft survival rates did not differ in African American deceased-donor kidney transplant recipients [ 43 ]. Another study has shown that alemtuzumab induction eliminates the posttransplant survival disparity between White and African American recipients by improving graft survival in all recipients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assert that alemtuzumab may be a good choice for high risk black transplant recipients. Although, alemtuzumab already has proven its usefulness in this regard in previous study [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…We are not the first to show the reduction of ethnic disparities between AA and White recipients beyond the first posttransplant year after induction with alemtuzumab. 25 Smith and associates found that, in patients who did not receive alemtuzumab, White recipients had significantly lower rates of graft failure than AA recipients (14.9% vs 44.4%; P = .0156). 25 However, in patients who received alemtuzumab, no significant differences in allograft failure rates between White and AA patients existed (5.7% vs 9.4%; P = .8248).…”
Section: Figure 3 Patient Survival By Race/ethnicitymentioning
confidence: 99%
“…Smith and associates proposed that the simplicity of alemtuzumab induction therapy (a onetime, perioperative dose) could have an effect on increasing patient adherence and thereby increasing favorable outcomes. 25 As mentioned previously, genetic factors seem to play a role in increasing the risk of chronic kidney disease and end-stage renal disease in AA patients. [27][28][29][30][31] Therefore, it is plausible that genetic factors could also be partially responsible for improving outcomes in AA patients induced with alemtuzumab.…”
Section: Figure 3 Patient Survival By Race/ethnicitymentioning
confidence: 99%